Premutation Allele Combined with Caregiver Distress Factor Increase the Risk of Depression in Fragile X Carriers: Indonesia Setting - Winarni, Tri Indah; Sumekar, Tanjung Ayu; Wibowo, Susilo; Hagerman, Randi J.; Faradz, Sultana M.H. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
This study was done to determine the risk of anxiety and depression symptoms among fragile X premutation carriers. Hamilton anxiety rating scale (HARS) and Hamilton depression rating scale (HDRS) was administered by trained physicians to measure the severity of anxiety and depression symptoms, respectively. Caregiver distress factors which directly contribute to caregiver burden in particular degree of relationship with the child, number of FXS child, child institutional/educational status, number of hours spent providing care per day, and the degree of illness severity were documented. Thirty-one fragile X carriers (27 females, 4 males), aged 32-77 years participated in this study. Only 3.2% had anxiety symptoms, while depression symptoms were identified in 35.5% carriers. Number of hours of providing care/day were significantly associated with depression symptoms (p<0.001). The prevalence ratio (PR) of depression among individuals who had a distress score above cut-off was 3.2 (95% CI= 1.2 to 8.5) compared to those who had a distress score below cut-off with p=0.02. Fragile X premutation carriers are at a greater risk to develop depression symptoms related to the hours spent in caring for children with fragile X syndrome (FXS).